Formulation and Effectiveness Testing of Mosquito Repellent Spray Combination of Citrusev Oil (Cymbopogon nardus) and Patchouli Oil (Pogostemon cablin) - Widya Ariati (Nusantara Scientific Medical, 2023)
Dengue fever is a health problem caused by the dengue virus dengue virus whose problem has not been resolved. Various attempts have been made to prevent dengue fever, one of which is chemical-based insecticides, but the use of chemicals can cause side effects ranging from mild to severe. The purpose of this study was to increase the use of natural ingredients as an alternative to mosquito repellents to minimize side effects and determine the effectiveness of the spray repelency against Aedes aegypti mosquitoes. This research method used an experimental approach using 20 mosquitoes, which were divided into five groups, namely formulation I (10% lemonggrass oil and 2% pathouli oil), formulation II (10% lemonggrass oil and 4% pathouli oil), formulation III (10% lemonggrass oil and 6% pathouli oil), control (-) ( propylene glycol and ethanol 96%) and control (+) (soffel spray) were each given the same treatment. The mist was sprayed on the arm, put in the test cage, and counted the number of mosquitoes perched on the arm for 5 minutes. The percentage of mosquito repellent power in fomulation I am 69%, formulation II is 76%, formulation III is 92%. The data were analyzed by using one-way ANOVA using the LSD (least significant difference) test; there were substantial differences between the treatment group and the level of effevtiveness of the repulsion againts the Aedes aegypti mosquito.